PERLINDUNGAN HUKUM TERHADAP OBJEK WAKAF BENDA BERGERAK - Gita Pratiwi; A.M Hasan Ali (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2022)
This study aims to explain the implementation of share waqf carried out at the Dompet Dhuafa institution, in addition to explaining the legal protection of the permanence of the object of share waqf in Law No. 41 of 2004 from the regulatory and technical aspects of the institution. This study uses a qualitative method by conducting an assessment of regulations, books, and contemporary fiqh books as a source of data in the preparation of writing this thesis. The results of the study show that in terms of regulation, Law Number 41 of 2004 concerning Waqf does not regulate the legal protection of the permanence of the waqf object. Meanwhile, in technical matters in Dompet Dhuafa, the institution in providing protection for the object of share waqf by managing it does not use the trading method, so that there is no capital loss